2004
DOI: 10.1073/pnas.0401860101
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin-associated protein 1 regulates inhibitory synaptic transmission by modulating γ-aminobutyric acid type A receptor membrane trafficking

Abstract: ␥-Aminobutyric acid type A receptors (GABAARs) are the major sites of fast synaptic inhibition in the brain. An essential determinant for the efficacy of synaptic inhibition is the regulation of GABA A R cell surface stability. Here, we have examined the regulation of GABA AR endocytic sorting, a critical regulator of cell surface receptor number. In neurons, rapid constitutive endocytosis of GABA ARs was evident. Internalized receptors were then either rapidly recycled back to the cell surface, or on a slower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
204
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(207 citation statements)
references
References 38 publications
3
204
0
Order By: Relevance
“…Thus, we concluded that Hap1 not only sequesters but also stabilizes Dcaf7 in the cytoplasm by inhibiting its degradation by the UPS. Because Hap1 can protect internalized receptors from lysosomal degradation (11,(29)(30)(31), Hap1 may stabilize its binding partners from subsequent degradation through either the lysosome or UPS.…”
Section: Hap1 Stabilizes the Protein Level Of Dcaf7 By Inhibiting Itsmentioning
confidence: 99%
“…Thus, we concluded that Hap1 not only sequesters but also stabilizes Dcaf7 in the cytoplasm by inhibiting its degradation by the UPS. Because Hap1 can protect internalized receptors from lysosomal degradation (11,(29)(30)(31), Hap1 may stabilize its binding partners from subsequent degradation through either the lysosome or UPS.…”
Section: Hap1 Stabilizes the Protein Level Of Dcaf7 By Inhibiting Itsmentioning
confidence: 99%
“…Endocytic recycling assays were performed essentially as described (Ehlers, 2000;Kittler et al, 2004). For measurements of total surface expression, cortical neurons (DIV 10-13, ≥ 3 replicate 6-cm plates/genotype) were incubated for 30 min with 100 μg/ml leupeptin in media, washed with PBS (+ CaCl 2 /MgCl 2 ), followed by incubation with 1 mg/ml sulfo-NHS-SS-biotin (Pierce, Rockford, IL) in PBS for 20 min on ice.…”
Section: Analysis Of Endocytic Recycling By Surface Biotinylation Of mentioning
confidence: 99%
“…Upon internalization, receptors are either reinserted into the plasma membrane or targeted for degradation (10). The balance between these two processes is critical for determining the number of receptors expressed at synapses and hence neuronal excitability (11).…”
mentioning
confidence: 99%
“…All cell types were transfected by nucleofection as described in ref. 10. See SI Materials and Methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation